Identification of Challenges to the Availability and Accessibility of Opioids in Twelve European Countries: Conclusions from Two ATOME Six-Country Workshops - Linge-Dahl, Lisa; Vranken, Marjolein; Juenger, Saskia; North, Kate; Scholten, Willem; Payne, Sheila; Radbruch, Lukas (Mary Ann Liebert inc, 2015)
BACKGROUND: Access to many controlled medicines is inadequate in a number of European countries. This leads to deficits in the treatment of moderate to severe pain as well as in opioid agonist therapy. OBJECTIVE: The study objective was to elaborate the reasons for this inadequacy. The work plan of the Access to Opioid Medication in Europe (ATOME) project included two six-country workshops. These workshops comprised a national situational analysis, drafting tailor-made recommendations for improvement and developing action plans for their implementation. METHODS: In total, 84 representatives of the national Ministries of Health, national controlled substances authorities, experts representing regulatory and law enforcement authorities, leading health care professionals, and patient representatives from 13 European countries participated in either one of the workshops. The delegates used breakout sessions to identify key common challenges. Content analysis was used for the evaluation of protocols and field notes. RESULTS: A number of challenges to opioid accessibility in the countries was identified in the domains of knowledge and educational, regulatory, legislative, as well as public awareness and training barriers that limit opioid prescription. In addition, short validity of prescriptions and bureaucratic practices resulting in overregulation impeded availability of some essential medicines. Stigmatization and criminalisation of people who use drugs remained the major impediment to increasing opioid agonist program coverage. CONCLUSIONS: The challenges identified during outcomes of the workshops were used as the basis for subsequent dissemination and implementation activities in the ATOME project, and in some countries the workshop proceedings already served as a stepping-stone for the first changes in regulations and legislation.
Keywords: Analgesics, Opioid; Controlled Substances; Europe; Health Policy; Health Services Accessibility; Humans; Pain; Palliative Care; Reimbursement Mechanisms; Journal Article; Research Support, Non-U.S. Gov't; Taverne; SDG 3 - Good Health and Well-being